Changes in blood parameters and metabolism in bullfrog tadpoles, Lithobates catesbeianus, (Shaw, 1802) after exposure to the Sorocaba River (São Paulo, Brazil) water - Utsunomiya, Heidi Samantha Moraes; Ferraz, João Victor Cassiel; Fujiwara, Gabriel Hiroshi; Gutierres, Davi Marques; Fernandes, Isabela Ferreira; de Lacerda Valverde, Bruno Serra [UNESP]; de Oliveira, Classius [UNESP]; Franco-Belussi, Lilian; Fernandes, Marisa Narciso; dos Santos Carvalho, Cleoni (Springer Nature, 2023)
This study evaluated the genetic damage, oxidative stress, neurotoxicity, and energy metabolism in bullfrog tadpoles (Lithobates catesbeianus) exposed to water from two sites of the Sorocaba River, Ibiúna (PI), and Itupararanga reservoir (PIR), in summer and winter. After 96-h exposure, the erythrocyte number decreased in PI and increase in PIR in summer. Bullfrogs show oxidative unbalance (liver, kidney, and muscle), with alterations in the nitric oxide synthase and glucose 6-phosphate dehydrogenase. Cholinesterase increased in the brain in PI and PIR in the summer and decreased in PI in the winter. It also increased in the muscle in both PI and PIR in the winter. Tadpoles show alterations in the activity of the metabolic enzymes (liver, kidney, and muscle), such as phosphofructokinase, pyruvatokinase, malate dehydrogenase, and lactate dehydrogenase; and in the amount of glucose and triglycerides metabolites. Exposure to the Sorocaba River reflected a stressful situation for L. catesbeianus as the changes caused to their metabolism associated with oxidative stress and neurotoxicity may have effects on the development of tadpoles.
Keywords: Amphibians; Erythrocytes; Glycolytic enzymes; Neurotoxicity; Oxidative stress